Study on the nuclear shield behaviors of basalt/carbon fibers reinforced PbO blended epoxy matrix composite – A novel material for thermal insulation applications - Raja Thandavamoorthy; Yuvarajan Devarajan (Nuclear Engineering and Technology)
This study introduces a novel composite material engineered for thermal insulation, specifically in environments requiring radiation shielding. The composite is composed of basalt and carbon fibers reinforced varying with lead oxide (PbO) nanoparticles for five different composite laminates, all integrated into an epoxy matrix. The research primarily focuses on evaluating the composite's thermal insulation capabilities, gamma-ray attenuation effectiveness, and microstructural characteristics. Mechanical testing reveals that the incorporation of basalt and carbon fibers significantly enhances the composite's tensile strength and modulus. Thermal analysis demonstrates the composite's excellent insulation properties, attributed to the synergistic effects of the fibrous reinforcement and the epoxy matrix, which effectively reduce thermal conductivity. Gamma attenuation tests indicate a substantial improvement in radiation shielding effectiveness with the addition of lead oxide nanoparticles. The composite exhibits improved gamma-ray attenuation compared to conventional materials, due to the high atomic number of lead, which enhances photon absorption and scattering mechanisms.Microstructural analysis provides detailed insights into the composite's structure. Morphological images show a uniform dispersion of PbO nanoparticles and strong adhesion between the fibers and the matrix. Elemental analysis confirms the elemental composition, highlighting the successful integration of PbO nanoparticles, which significantly enhances radiation shielding.